Pengembangan Gateway LoRa-MQTT untuk Transmisi Data Dua Arah antara Wireless Sensor Network dan Cloud Server - Dhiza Wahyu Firmansyah; Mochammad Hannats Hanafi Ichsan; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wireless sensor network is one of the main supporters in the development of the internet of things. One of the most widely used communication modules on wireless sensor networks is LoRa. LoRa has the advantage of being able to communicate over a large area and low power consumption. LoRa has the disadvantage of not being able to send data directly to the cloud server, so a gateway is needed to bridge the transmission. Communication from the gateway to the cloud is using the MQTT protocol. The MQTT protocol was chosen because it is lightweight and easy to use. In previous research has successfully implemented a gateway to bridge the transmission of data from the LoRa communication module to the MQTT protocol. However, it still has the disadvantage of only being able to communicate one way from the sensor node to the cloud. With this research, a LoRa-MQTT gateway is created that can communicate both ways from the sensor node to the cloud and from the cloud to the sensor node. Functionality testing is performed so the system can run as needed. Performance testing is carried out to determine the effect of distance and data size on system performance. The results of performance testing indicate that the longer distance does not necessarily result in a longer data transmission delay. However, it caused a decrease in the data transmission succes ratio.